Multiple Biogenic Amine Receptor Types Modulate Spider, Cupiennius salei, Mechanosensory Neurons - Sukumar, Vaishnavi; Liu, Hongxia; Meisner, Shannon; French, Andrew S.; Torkkeli, Päivi H. (Frontiers in Physiology, 2018)
The biogenic amines octopamine (OA), tyramine (TA), dopamine (DA), serotonin (5-HT) and histamine (HA) affect diverse physiological and behavioral processes in invertebrates, but recent findings indicate that an additional adrenergic system exists in at least some invertebrates. Transcriptome analysis has made it possible to identify biogenic amine receptor genes in a wide variety of species whose genomes have not yet been sequenced. This approach provides new sequences for research into the evolutionary history of biogenic amine receptors and allows them to be studied in experimentally accessible animal models. The Central American Wandering spider, Cupiennius salei, is an experimental model for neurophysiological, developmental and behavioral research. We identified ten different biogenic amine receptors in C. salei transcriptomes. Phylogenetic analysis indicated that, in addition to the typical receptors for OA, TA, DA and 5 HT in protostome invertebrates, spiders also have α1- and α2-adrenergic receptors, but lack TAR2 receptors and one invertebrate specific DA receptor type. In-situ hybridization revealed four types of biogenic amine receptors expressed in C. salei mechanosensory neurons. We used intracellular electrophysiological experiments and pharmacological tools to determine how each receptor type contributes to modulation of these neurons. We show that arachnids have similar groups of biogenic amine receptors to other protostome invertebrates, but they lack two clades. We also clarify that arachnids and many other invertebrates have both α1- and α2-adrenergic, likely OA receptors. Our results indicate that in addition to an OAβ-receptor that regulates rapid and large changes in sensitivity via a Gs-protein activating a cAMP mediated pathway, the C. salei mechanosensory neurons have a constitutively active TAR1 and/or α2-adrenergic receptors type that adjusts the baseline sensitivity to a level appropriate for the behavioral state of the animal by a Gq-protein that mobilizes Ca2+.